To Read or Not to Read: Understanding the Emergence of Aliteracy - Wissink, Barbara (Advances in Social Sciences Research Journal, 2020)
This case study research studied the complex construct of aliteracy in upper elementary students. Six students were selected from the fourth, fifth, and sixth grades, after the analysis of the following quantitative sources: report card grades, standardized test scores, and the Motivation to Read Questionnaire (MRQ) results. After the selection of students, qualitative data was provided by the six students, eleven parents, and five classroom teachers. Questionnaires, interviews, observations, and reading logs comprised the qualitative data, which was analyzed using grounded theory methods. The Emergence of Aliteracy Theory emerged as a result, which clarified how the home and classroom environments produce a unique set of commonalities that underpin the emergence of aliteracy, and possibly impact students’ academic learning.